POLITICAL AND LEGAL FOUNDATIONS OF INFORMATION SECURITY IN THE MODERN WORLD - Ahmedova, Shafag; Shirinov, Azer (Revista Gênero e Interdisciplinaridade, 2020)
The analysis of the current political and legal foundations of information security and comparison of its different historical stages have proved that many factors directly affect this process. They include inter-state historical relations and the world order, the struggle of various countries and regions for resources, the development of information and communication technologies, as well as the self-awareness of people. The authors of the article have concluded that information security lays the basis for state security in general and increases its power. The level and nature of communication between countries and their blocs are determined by the ability to influence each other through a system of propaganda and communication routes, including goods, services, the education system, scientific studies and social networks. Cybercrime can be combatted not only through toughening political and legal restrictions but also through forming a global humanitarian approach to human values, which is ensured by the education system, the exchange of universal cultural values and the formation of new human qualities. The political and legal foundations of modern information security are as follows: historical relations between various states and regions; the current world order as the leading factor in forming the concept of information security; the power of each state and its role in the international security system as a political actor; the nature and development of information society in each region of the world; a set of international laws and treaties regarding the use of information, its preservation and disposition; the legal framework of each state; general trends in the formation of the global information space and its features associated with information and communication technologies. Information can work to the benefit only if different countries and regions cooperate since their interdependence grows each year, including in the sphere of information support. To obtain these results, system analysis of the legal framework of economic security, both in individual countries and internationally, as well as an abstract logical analysis of the practice of making political decisions to ensure information security were used. The rules and guidelines of information security, described in the scientific literature, as well as applied in practice in individual countries, have been studied.